Cervical firearm injury: internal and external bilateral jugular ligatures “a complex case of brain venous drainage and congestion”: clinical case report (Revista Chilena de Rehabilitación y Actividad Física, 2021)
Penetrating neck injuries account for about 5-10% of all cases of trauma that occur in the emergency department and result in significant mortality. Cervical components most often injured in penetrating trauma are related to vascular lesions (21-27%), followed by the spinal cord (16%) and the aero-digestive tract (6-10%), such as the larynx or trachea and the oropharynx or esophagus. Most commonly, these injuries are secondary to gunshot and gunshot wounds. Vascular trauma of large cervical veins is exceptional, highly morbid and has serious consequences on brain venous drainage. We present a case of cervical wounds with a ruptured pharynx, esophagus, back wall of trachea and section of both external and internal jugulars being necessary their ligation. Cerebral venous drainage in a few minutes has changed its pattern and flow being vague at first to locate this as an anatomical map of cerebral venous drainage, however, a brain venous congestion with intracranial hypertension is expected the vast majority of the time interpreted with “Brain Pseudotumor”.
Keywords: Vascular injury; Penetrating injury; Vascular trauma